Development and Preliminary Validation of a New Type 1 Diabetes Adjustment Scale (DAS-1) - Rivas, Teresa; Carreira, Mónica; Domínguez-López, Marta; Ruiz de Adana, Maria Soledad; Anarte, María Teresa (Frontiers in Psychology, 2020)
Background: This study focuses on the development and validation of a new Type 1 Diabetes Adjustment Scale (DAS-1). Method: Two hundred and four participants aged 15-65 with type 1 diabetes completed the self-report measures of the DAS-1, which includes clinical and psychological variables. Results: Exploratory and robust confirmatory factor analysis detected a unidimensional structure of the item scores. The omega coefficient was 0.91 and test–retest reliability was 0.87. Classifying subjects as in a Positive or Negative mood state, ROC analysis yielded an optimal cut-off of 50 for the DAS-1 scores, with a clinical accuracy of AUC=0.85. The DAS-1 demonstrated evidence of good reliability and acceptable construct validity. Conclusions: The DAS-1 demonstrated good clinical utility, good sensitivity and adequate specificity. Clinical and theoretical implications of these results are discussed.